Single mothers and their sense of purpose and meaning in life - Klimek, Lilianna; Barabas, Magdalena (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2015)
The theoretical context of these reflections is based on K. Popielski’s concept of the noetic dimension of personality and existence. The research was conducted among women living in residential homes for single mothers. Their sense of purpose and meaning in life was assessed with the use of J.C. Crumbaugh and L.T. Maholick’s Purpose in Life Scale (PIL). The collected material was evaluated using quantitative analysis.
Keywords: sense of life; single mothers